Gateway to Opportunity: A Promising Summer Youth Employment Model to Address Local Workforce Needs - Williams, Nikki; Hawes, Susy (Maine Policy Review, 2021)
Throughout Maine, employers struggle to find workers with in-demand skills and competencies. Concurrently, work-eligible youth are often unable to find skill-building employment experiences. The Gateway to Opportunity (G2O) program is a comprehensive youth-adult partnership model developed in Portland, Maine, that is designed to address both of these challenges. G2O connects high-school-aged young people with paid, work-based learning projects at Maine-based businesses and nonprofits. The model for this program is based on national best practices and lessons learned from multiple highly successful summer youth employment initiatives led by Brandeis University’s Center for Youth and Communities from 2011 to 2013. This article highlights the development and growth of this program model and explores how innovative work-based learning programs such as G2O are critical for Maine’s workforce and local economy.